The Proverbs in “Gulzar “for the author Taher Shoshi - Mohammed, Abdi H.; Qader, Ramathan H.; Haji, Nawzad A. (Humanities Journal of University of Zakho, 2016)
The present research entitled (The proverbs in “Gulzar “for the author Taher Shoshi) deals with the embodiment of proverbs in “Gulzar “which contains about 10000 lines of poetry. This poetry investigates the life of Prophet Mohammed, the history of his family and the Islam religion until the fifth year of Prophet Immigration. This work implies a lot of advises and sermons written in language of layman’s by which everyone can understand and make use of it. The proverbs have been written for the people in their language and many of prudence and proverbs can be found in Gulzar. The proverbs which are taken from Kurdish folklore whether directly or indirectly have expression in poetry. The role and embodiment of proverbs in Kurdish poetry have been briefly investigated. And the way in which these proverbs have been employed in Kurdish poetry have been investigated in details.